(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This research was conducted in Delhi manufacturing sector, with data collected from 77 employees from six manufacturing companies. Retention is not influenced by gender, experience, or the nature of the employee’s work, according to the research. However, the study found that retention is influenced by age, education level, designation of workers, and average monthly income of employees.